Aetiology-specific comparison of long-term outcome of deep anterior lamellar keratoplasty for corneal diseases. Issue 9 (23rd December 2015) - Ogawa, Akiko; Yamaguchi, Takefumi; Mitamura, Hiroto; Tomida, Daisuke; Shimazaki-Den, Seika; Murat, Dogru; Satake, Yoshiyuki; Shimazaki, Jun
Abstract : Aims: To evaluate the long-term outcome of deep anterior lamellar keratoplasty (DALK) for the treatment of herpetic keratitis, keratoconus, stromal scars and corneal dystrophies. Methods: This retrospective consecutive case study includes 275 consecutive eyes of 254 patients who underwent DALK; 35 eyes with herpetic keratitis, 114 eyes with stromal scar, 93 eyes with keratoconus and 67 eyes with corneal dystrophy. Exclusion criteria included therapeutic DALK for the treatment of descemetocele or infectious keratitis, and eyes with limbal stem cell deficiency. Patients were examined at 1, 3 and 6 months, and 1, 3 and 5 years after DALK. Graft survival rate, best corrected visual acuity (BCVA), endothelial cell density (ECD) and postoperative complications were evaluated. Results: The mean postoperative follow-up duration was 51±41 months. The graft survival rate of all subjects was 96.8% at 1 year, 89.9% at 3 years, 83.5% at 5 years and 74.1% at 10 years. At 6 months, BCVA significantly improved from 1.14±0.54 to 0.22±0.21 in the keratoconus group, from 1.13±0.60 to 0.44±0.54 in the herpes group, from 1.00±0.59 to 0.49±0.38 in the stromal scar group and from 1.04±0.52 to 0.32±0.29 in the corneal dystrophy group (all, p<0.0001). BCVA stabilised after 6 months thereafter up to 5 years. ECD decreased just after DALK and maintained >1000 cell/mm 2 at 5 years in all groups. Conclusions: DALK provides good visual acuity with slight ECD decrease over long term in all groups.